Purification and characterization of recombinant human p50csk protein-tyrosine kinase from an Escherichia coli expression system overproducing the bacterial chaperones GroES and GroEL. - Amrein, K E (1995)
An Escherichia coli expression system overproducing the bacterial chaperones GroES and GroEL was engineered and has been successfully used to produce large quantities of the recombinant human protein-tyrosine kinase p50csk. The co-overproduction of the two chaperones with p50csk results in increased solubility of the kinase and allows purification of milligram amounts of active enzyme. Analysis of the purified protein by SDS/polyacrylamide gel electrophoresis reveals a single band with an apparent molecular mass of 50 kDa, indicating that recombinant human p50csk has been purified to near homogeneity. The purified enzyme displays tyrosine kinase activity as measured by both autophosphorylation and phosphorylation of exogenous substrates. Biochemical properties, including in vitro substrate specificity and enzymatic characteristics of the enzyme, have been assessed and compared with those of members of the Src family of protein-tyrosine kinases. Results indicate that p50csk and p56lck have different substrate specificities and that p50csk and p60c-src have similar kinetic parameters. The successful production and purification of an enzymatically active form of p50csk will enable further characterization of this important kinase and allow clarification of its physiological role. In addition, the results suggest that the approach described may be generally applicable to improve the solubility of recombinant proteins which otherwise are produced in an insoluble form in E. coli.